Synthesis, characterization, micellar and drug release properties of dihydrophilic / amphiphilic poly (n-isoproplacrylamide) -b-poly (vinyl acetate )/ poly (vinyl alcohol) diblock copolymers - Helvacıoğlu, Ekmel. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2011., 2011)
In this study, poly(vinyl acetate)-b-poly(N-isopropylacrylamide) block copolymers, which were previously synthesized by macromolecular design via interchange of xanthates (MADIX) process, are partially or fully hydrolyzed to yield poly(vinyl acetate)/poly(vinyl alcohol)-b-poly(N-isopropylacrylamide) thermoresponsive amphiphilic/dihydrophilic block copolymers for the first time. In the next stage, the aqueous micellar solution and drug release properties of the polymeric products are studied. The products are characterized by 1H NMR and Fourier Transform Infrared Spectroscopy (FTIR) for proving and calculating per cent hydrolysis values for partial and full hydrolysis. About 70% partial hydrolysis for obtaining dihydrophilic thermoresponsive block copolymers and full hydrolysis for obtaining amphiphilic thermoresponsive block copolymers are successfully perfromed. The aqueous micellar solutions are analyzed by Dynamic Light Scattering Particle Size Analyzer (Nano-PSA) and Environmental Scanning Electron Microscope (ESEM) for checking stability of micelles and determining micelle sizes and temperature effect on micelles There is a good agreement between results derived from both analyses. Differential Scanning Calorimetry (DSC) analyses are performed to find Tg of block copolymers, and lower critical solution temperature (LCST) values, which are not necessarily influenced by hydrolysis. A very low CMC value, which is typically exhibited by block copolymers, is found by Fluorescence Spectroscopy. Drug loading capability and in vitro release properties of micelles are analyzed via UV-Visible Spectroscopy with the usage of a hydrophobic drug, Ezetimibe. The experiment exhibits an expected high loading and slow release type behavior of the block copolymer micelles.
Keywords: Photovoltaic cells.; Solar cells.; Vinyl acetate.